Characteristics of effective teacher education in low- and middle-income countries: What are they and what role can EdTech play? - Allier-Gagneur, Zoe; McBurnie, Chris; Chuang, Rachel; Haßler, Björn (EdTech Hub, 2020)
This paper analyses a range of literature reviews to identify characteristics of effective teacher education, including focusing on practical subject pedagogy; incorporating peer support and; creating a coherent policy environment.
previousDOI: 10.5281/zenodo.4762301 previousDOI: 10.5281/zenodo.3873462 EdTechHub.Copy: 2129771:237CSM4W EdTechHub.Copy: 2129771:237CSM4W KerkoCite.ItemAlsoKnownAs: 2129771:237CSM4W 10.5281/zenodo.3873462 10.5281/zenodo.4762301 10.53832/edtechhub.0007 2129771:237CSM4W 2129771:RMWSKUI5 2339240:2Y5CD84V 2339240:4P99D7MN 2339240:5P9STQIK 2339240:8DMB3N8E 2339240:AQFSE6DQ 2339240:K3RVT7JU 2339240:WP59YJ57 2339240:ZV7A4BWS 2405685:3T894KD8 2405685:3TKLS2TH 2405685:3UXB7ZWR 2405685:BHY8AJBY 2405685:I62EYSDT 2405685:LNUMVYFV 2405685:P5MEX8KB 2405685:R9VVKUH5 2405685:T48HFJM4 2486141:IX4B74H9 2534378:T2X9U5AV
Keywords: E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _forthcoming; _zenodoETH:submitted; _zenodoODE; docs.opendeved.net; dode_eth-src-eth; dode_eth-trf2-dode

Messaging Apps, SMS, and Social Media: A Rapid Evidence Review - Jordan, Katy; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of existing research on the use of mobile phone-based messaging (including SMS, and messaging through apps such as WhatsApp) to support education in low- and middle-income countries (LMICs). This topic was chosen as the focus for a RER in response to the Covid-19 pandemic and school closures, as this form of technology has been adopted as part of some countries’ methods of providing continuing education during closures and disruption. As such, the overall purpose of this document is to summarise the existing research literature around messaging, so that the existing evidence can be used to inform ongoing responses to the pandemic. The findings are intended to be of use to educational decision makers, including donors and those in government and NGOs, to inform responses to the current pandemic.
ZenodoArchiveID: 4556938 PreviousDOI: 10.5281/zenodo.4058181 PreviousDOI: 10.5281/zenodo.4477015 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.4058181 10.5281/ZENODO.4556938 10.5281/zenodo.4477015 10.5281/zenodo.4556938 2339240:8QFLYEYK 2339240:ATYZFQ8R 2339240:CUBEJEWS 2339240:LCAUL9ZC 2339240:NISQD6JT 2339240:T2Z992XW 2339240:XMQV9Y56 2339240:YGQCMSDP 2405685:2GE8ESCR 2405685:4G8DT7ZB 2405685:4JM6QWPH 2405685:5NMCR3LL 2405685:EQVI8NMV 2405685:IU849P3E 2405685:MMTHETFR 2405685:PY3CXCH9 2405685:QSD5LYSF 2405685:XHBPFYVC 2405685:Z7P9NRWJ
Keywords: Covid-19; LMICs; SMS; Social media; TPD; WhatsApp; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; educational technology; mobile learning; refugee education; teacher professional development; text message; ⛔ No DOI found

Position paper: Using EdTech to support teacher education and professional development in low- and middle-income countries (internal working paper). - Hennessy, Sara; Koomar, Saalim; Kreimeia, Adam (EdTech Hub, 2020)
ZenodoArchiveID: 5652080 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5652080 2339240:VJNSF4EV 2339240:Z6ZIBS2B 2405685:6E2K4GGE
Keywords: _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _dont_post_PDF

Effective Teacher Education in Low-Connectivity Settings: A Curated Resource List - Koomar, Saalim; Allier-Gagneur, Zoé; McBurnie, Chris (EdTech Hub, 2020)
This list curates resources — both tools and initiatives — that can be adapted to support teacher education in low-connectivity settings, a prevailing challenge in Madagascar. Each example identifies the challenges; necessary prerequisites; pros and cons and; costs and impact assessment data where possible.
ZenodoArchiveID: 5652141 previousDOI: 10.5281/zenodo.4762283 previousDOI: 10.5281/zenodo.4762283 2405685:UQSMRFBF previousDOI: 10.5281/zenodo.3407498 EdTechHub.Source: DOI: DOI:10.5281/zenodo.4762283 2405685:UQSMRFBF EdTechHub.Source: <this> shortDOI: 10/ghgnd8 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3407498 10.5281/zenodo.5652141 10/ghgnd8 2129771:U3XSZB5F 2339240:CRCGCNE9 2405685:UQSMRFBF
Keywords: C:Madagascar; E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; W:Low connectivity and/or electricity; _DOILIVE; _EdTechHub_Output; _MELA_seen; _zenodo:submitted; _zenodoETH; _zenodoETH:submitted; dode_eth-src-eth; dode_eth-trf2-dode

Open Educational Resources in Africa: A Curated Resource List - Koomar, Saalim; Jull, Stephen (EdTech Hub, 2020)
This curated list defines Open Rducational Resources (OER), offers background on open-source licensing, and provides a review of OER that can be used in the sub-Saharan African context.
ZenodoArchiveID: 5652135 previousDOI: 10.5281/zenodo.3906041 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3906041 10.5281/zenodo.5652135 2339240:546TH9C9 2339240:E5AXYSMF 2339240:RKVKV84H 2405685:4ER9WB55 2405685:7JSP4PFC 2405685:DMSLLEQV 2405685:HZ5X5A4W 2405685:V44Z75Z3 2405685:VVB3BRE5
Keywords: C: Ghana; F: Helpdesk response; H: Open resources; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH

Characteristics of effective teacher education in low- and middle-income countries: an annotated bibliography (HDR10C) - McBurnie, Chris; Allier-Gagneur, Zoe; Haßler, Björn (EdTech Hub, 2020)
previousDOI: 10.5281/zenodo.3873460 EdTechHub.Copy: 2129771:3AV78BC7 EdTechHub.Copy: 2129771:3AV78BC7 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3873460 10.53832/edtechhub.0008 2129771:3AV78BC7 2339240:FE5LM4QS 2405685:KXY7Q6VT
Keywords: E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

EdTech Initiatives Focused on Classrooms and Teachers: A Curated List for Rwanda - Chuang, Rachel; Koomar, Saalim (EdTech Hub, 2020)
This document was produced in response to a request from the FCDO Rwanda team for a curated list of EdTech initiatives related to the following focus areas: 1. Classroom software 2. Teacher education 3. School administration.
ZenodoArchiveID: 4762316 previousDOI: 10.5281/zenodo.4050155 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.4762316 10.5281/zenodo.3990369 10.5281/zenodo.4050155 10.5281/zenodo.4762316 10/ghgk62 2339240:86AAWUD3 2339240:BMRM6MNQ 2339240:RYU57YK3 2405685:BMDY65UF 2405685:CHX3W9RE 2405685:WGYWI78R
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _zenodo:submitted; _zenodoETH; _zenodoETH:submitted

Using Education Technology to Support Students with Special Educational Needs and Disabilities in Low- and Middle-Income Countries - Coflan, Caitlin Moss; Kaye, Thomas (EdTech Hub, 2020)
This brief focuses on how policymakers can make decisions about EdTech to support learners with special educational needs and/or disabilities (SEND) while offering policymakers the rationale and tools to move towards an inclusive approach. It also includes a detailed annex with descriptions, costs, availability, and examples of accessible and assistive technologies.
ZenodoArchiveID: 3744581 previousshortDOI: 10/ghgng7 previousDOI: 10.5281/zenodo.3744581 EdTechHub.Source: 2405685:2WY8H4WW EdTechHub.Source: <this> shortDOI: 10/ghgng7 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3744581 10.5281/zenodo.3744581 10.53832/edtechhub.0021 10/ghgng7 2129771:QEIBUIQH 2339240:3NRFPYGI 2339240:TK94XQR9 2339240:XJRI6FW3 2339240:Y635S3D4 2339240:Z7XXM8CG 2339240:ZZ8ISXSK 2405685:2WY8H4WW 2405685:6FFSC2Z8 2405685:DI4SGTPH 2405685:FLHI5BHC 2405685:FVE6PDBB 2405685:GG9HHSDL 2405685:PXAIRTEK 2405685:RLBPSG29
Keywords: F: Helpdesk response; L:Special education needs and disabilities (SEND); LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v1; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-dode

An EdTech reading list from the Helpdesk team: Autumn 2020 (EdTech Hub, 2020)
In this blog post, we summarise six new publications from the Helpdesk and what we have learned about monitoring and evaluation, curriculum reform, blended learning, and teacher education. As Covid-19 continues to affect learning around the world, our Helpdesk is seeing a shift in the requests we receive. Earlier, the bulk of requests were linked to short-term Covid responses. Now,…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707480 2405685:29RAGPFX 2405685:E2UQW73U
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Rolling Out a National Virtual Learning Environment - Adam, Taskeen; McBurnie, Chris; Haßler, Björn (EdTech Hub, 2020)
A virtual learning environment (VLE) is a virtual space designed to support teaching and learning and can resemble anything from a curated content repository to a synchronous video-enabled learning space. This technical note aims to inform the design and implementation of a VLE at a national level for basic education.
previousshortDOI: 10/ghgnf6 previousshortDOI: 10/ghgnf6 previousDOI: 10.5281/zenodo.3406132 previousshortDOI: 10/ghgnf6 EdTechHub.Source: 2405685:KWJRW62J EdTechHub.Source: <this> shortDOI: 10/ghgnf6 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3406132 10.5281/zenodo.3406132EdTechHub.ItemAlsoKnownAs: 10.53832/edtechhub.0010 10/ghgnf6 2129771:3H8JIJ9T 2129771:MG4TM5B3 2339240:CN8LY32H 2339240:EG4V9NYX 2339240:T37Q6QE6 2339240:W2B4DTPS 2405685:7EP4VHD7 2405685:B76WDWTE 2405685:KWJRW62J 2405685:QFMSIUXQ 2405685:Y4EVL7PR 2486141:TAPS8LVP
Keywords: F: Helpdesk response; H:Online learning; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v1; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Summarised Findings from the EdTech Hub Helpdesk - Chuang, Rachel; Moss Coflan, Caitlin (EdTech Hub, 2020)
As of December 2020, EdTech Hub’s Helpdesk has been active for nine months, responding to over 60 requests supporting decision-making on education technology. This document summarises our responses to six commonly asked questions across the topics of reaching marginalised learners, supporting teachers, and using EdTech to mitigate learning loss.
previousDOI: ​10.5281/zenodo.4299931 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4299931 10.5281/zenodo.4768560 2339240:CYPLQHH4 2405685:C49UMTX2 2405685:CWRFU9K9
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:image; _r:CopiedFromEvLib; _zenodoETH; _zenodoETH:submitted

Effective Use of EdTech for Remedial Learning Programmes: Considerations for Mongolia - Upadhyay, Arjun; Shoobridge, James; Moss Coflan, Caitlin (EdTech Hub, 2020)
This document was produced in response to a request from the World Bank Mongolia team to: 1. Outline the evidence of effective practices on remedial education generally. 2. Explore appropriate uses of EdTech to support remedial education. 3. Summarise the implications of these findings for Mongolia.
previousDOI: 10.5281/zenodo.3958080 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3958080 10.5281/zenodo.5651111 2339240:3DJBGPQM 2339240:AWK2HEZ5 2405685:IJGQTHH9 2405685:UMZVQ4TV 2405685:ZEDSYPGH
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _zenodo:submitted

Bangladesh Back-to-School Campaign - Kaye, Tom; Chuang, Rachel; Moss Coflan, Caitlin; Haßler, Björn (EdTech Hub, 2020)
The EdTech Hub received a request from the FCDO Bangladesh team to provide a topic brief identifying best practices from previous back-to-school campaigns following disruptions. Key themes of effective school re-openings are examined in the context of modalities used to deliver distance learning (e.g., radio, television).
ZenodoArchiveID: 3865298 previousshortDOI: 10/ghgk6p previousshortDOI: 10/ghgk6p previousDOI: 10.5281/zenodo.3865298 shortDOI: 10/ghgk6p KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3865298 10.53832/edtechhub.0020 10/ghgk6p 2129771:2BEHBMUH 2129771:C6TREICJ 2129771:GQ4U9R5Z 2129771:QFFBWT4D 2339240:H8RZC7AY 2339240:T5DE93E2 2405685:3HP24UTI 2405685:CEADG684 2405685:H52W8E9M 2405685:HFKVA2IQ 2405685:U2AQUAZ2 2486141:B8P7D4EU
Keywords: C:Bangladesh; COV:COVID and reopening of schools; E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; _cover:v1; _r:CopiedFromEvLib; _yl:g; _zenodo:submitted; _zenodoETH; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Your Questions Answered: Using Technology to Support Gender Equity, Social Inclusion and Out-Of-School Learning - Allier-Gagneur, Zoé; Moss Coflan, Caitlin (EdTech Hub, 2020)
EdTech Hub participated in a Girls’ Education Challenge webinar in May 2020, which welcomed stakeholders from countries including the UK, Kenya, Zimbabwe, and Nepal. The session focused on issues regarding gender and social inclusion during the Covid-19 crisis. This document provides answers to a list of 10 questions received from stakeholders.
previousshortDOI: 10/ghgng8 previousDOI: 10.5281/zenodo.3874247 EdTechHub.Source: 2405685:VX7UW757 EdTechHub.Source: <this> 2339240:KPL424XH shortDOI: 10/ghgng8 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3874247 10.5281/zenodo.3874247 10.53832/edtechhub.0025 10/ghgng8 2129771:LBII97HZ 2339240:2R8Z34D2 2339240:FT2TLP7Q 2339240:G93JLKST 2339240:J7DSQVEZ 2339240:QSKUJUNV 2339240:YK2KWXPL 2405685:2D6GK36K 2405685:48AAKD33 2405685:7VFMN2XM 2405685:G7ZB68PJ 2405685:I5WKHBZI 2405685:TP5CQYPQ 2405685:VX7UW757 2405685:YEVYTSJA 2405685:ZUDWQVKI
Keywords: F: Helpdesk response; L:Gender and education; L:Out-of-school populations; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v1; _r:CopiedFromEvLib; _zenodoETH; dode_eth-src-dode

Open Education Resources in Africa: A Curated Resource List - Koomar, Saalim; Jull, Stephen (Zenodo, 2020)
This curated list defines open educational resources, offers background on open source licensing, and provides a review of OER relevant to the context of Ghana in response to an EdTech Hub helpdesk request. This document does not intend to set out a comprehensive list of OER used by teachers, students, parents or other stakeholders; rather, this document will identify exemplars of OER provided they are relevant to the Ghanaian context and focus on: reaching marginalised learners through offline or online content; reaching marginalised learners through mass media; using OER for teacher education; further useful resources and methods of implementing OER.
KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3906041 10.5281/zenodo.3906041 2339240:35NW4SYR 2405685:VD8J4NCU

Radio: A Rapid Evidence Review - Damani, Kalifa; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of the existing literature on the use of radio in education in low- and middle-income countries (LMICs). The present RER has been produced in response to the novel 2019 coronavirus (COVID-19), and the resulting widespread shutdown of schools. It, therefore, highlights transferable insights that may be applicable to educational responses resulting from the limitations caused by COVID-19. Established approaches to delivering distance education have renewed salience during this period because many students cannot access schooling in a school building due to social distancing requirements. As one of the longest-serving and most accessible types of educational technology (EdTech), and one that has had some success in education delivery in an LMIC context that was affected by an epidemic, it is particularly useful to focus on radio (Barnett et al., 2018; Hallgarten, 2020). Notably, the RER aims neither to advocate nor discourage the use of radio in education in response to the COVID-19 pandemic. Instead, it provides an accessible summary of existing evidence on the topic so that educators, policy makers and donors might make informed decisions about the potential of radio in education delivery.
ZenodoArchiveID: 4556932 PreviousDOI: 10.5281/zenodo.4477141 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3948149 10.5281/ZENODO.4556932 10.5281/zenodo.4477141 10.5281/zenodo.4556932 2259720:DSXFK6JB 2339240:4JRWSL6I 2339240:8YVF7D5N 2339240:EPCMUN8C 2339240:FKFII8IK 2339240:H8YNQIY9 2339240:IJJ6TY76 2339240:QBDJ6U43 2339240:YIAFCN9T 2405685:5GBRDVHP 2405685:65UPSCK3 2405685:67BFM4C5 2405685:6CG6479A 2405685:DM6JSS9K 2405685:P8NUYK3M 2405685:PZHGV2XR 2405685:QBYZW7N2 2405685:RBUXXHAD 2405685:VHGNZV9N 2405685:X8BFH2K5 2405685:YMWE6FR6
Keywords: L:English UXZJW5DR; TAG:E:Primary education QIVZD2B2; TAG:E:Secondary education JS5BG2RE; TAG:F:Access W8TZWAGE; TAG:F:Educational data QWBAFGFR; TAG:F:Online and distance teaching and learning A32ARSFK; TAG:H:Audio and Radio QIAXGMEU; TAG:P:Teachers DAJFZBM8; TAG:W:Low connectivity and/or electricity KET3PKDI; _DOILIVE; _EdTechHub_Output; _GS:indexed; _L:English UXZJW5DR; _MELA_seen; _T:E:Primary education QIVZD2B2; _T:E:Secondary education JS5BG2RE; _T:F:Access W8TZWAGE; _T:F:Educational data QWBAFGFR; _T:F:Online and distance teaching and learning A32ARSFK; _T:H:Audio and Radio QIAXGMEU; _T:P:Teachers DAJFZBM8; _T:W:Low connectivity and/or electricity KET3PKDI; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH

The Use of Virtual Learning Environments and Learning Management Systems During the Covid-19 Pandemic - McBurnie, Chris (EdTech Hub, 2020)
This technical note aims to inform the use and development of virtual learning environments (VLE) in educational responses to the current health crisis. It considers the advantages and disadvantages of a number of existing VLEs and includes guidance on selecting an appropriate VLE.
ZenodoArchiveID: 5652169 previousZenodoArchiveID: 3805843 previousshortDOI: 10/gg7sqk previousDOI: 10.5281/zenodo.3805843 EdTechHub.Copy: 2129771:DQLDNQGU shortDOI: 10/gg7sqk KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3805843 10.5281/zenodo.3805843 10.53832/edtechhub.0023 10/gg7sqk 2129771:DQLDNQGU 2339240:IWW8CJZN 2339240:N5RG3WT2 2339240:QGMNZZER 2405685:53YEZE6A 2405685:933PQ5Q6 2405685:MHEB7LKZ 2405685:WBNK52L7
Keywords: COV:COVID and reopening of schools; COVID-19; Distance learning; EdTech; F: Helpdesk response; H: Distance education; LP: English; Learning management system; Remote learning; Virtual learning environment; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Using EdTech in Settings of Fragility, Conflict and Violence: A Curated Resource List - Koomar, Saalim; Moss Coflan, Caitlin; Kaye, Tom (EdTech Hub, 2020)
This curated list of resources collates interventions that effectively deploy education technology in settings of fragility, conflict and violence (FCV). This list explores effective uses of EdTech in FCV settings, emphasising interventions and evidence relevant to the Yemeni context and distance learning during the Covid-19 crisis.
previousshortDOI: 10/ghgng4 previousDOI: 10.5281/zenodo.3885806 EdTechHub.Source: 2405685:CMS6HPI8 EdTechHub.Source: <this> shortDOI: 10/ghgng4 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3875138 10.5281/zenodo.3885806 10.53832/edtechhub.0042 10/ghgng4 2129771:FCNVWJUI 2129771:VJXKA7AN 2339240:FEGWVFS3 2339240:FJ5LQ7QK 2405685:79LULMUU 2405685:BTWBKYN7 2405685:CMS6HPI8 2405685:HLCYI98H 2405685:RV5RNCII
Keywords: C:Yemen; F: Helpdesk response; LP: English; W:Fragile and conflict affected contexts; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

EdTech in Senegal: A Rapid Scan - Upadhyay, Arjun; Taddese, Abeba (EdTech Hub, 2020)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. These factors include the policy or vision for EdTech, institutional capacity, private sector partnerships, and digital infrastructure. The scans are intended to be comprehensive but are by no means exhaustive. The aim is to provide a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Liberia. This report is based primarily on desk research, with quality assurance provided by a country expert.
ZenodoArchiveID: 5652140 previousZenodoArchiveID: 3936687 previousshortDOI: 10/ghgnd2 previousDOI: 10.5281/zenodo.3936687 shortDOI: 10/ghgnd2 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3936687 10.53832/edtechhub.0037 10/ghgnd2 2339240:EHTSKIBR 2339240:YQHNWNMB 2405685:5P5HVP47 2405685:BBP57X2K 2405685:SKFMQF3F 2405685:XI5PXVB3
Keywords: C:Senegal; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; pu

EdTech in Liberia: A Rapid Scan - Upadhyay, Arjun; Taddese, Abeba (EdTech Hub, 2020)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. These factors include the policy or vision for EdTech, institutional capacity, private sector partnerships, and digital infrastructure. The scans are intended to be comprehensive but are by no means exhaustive. The aim is to provide a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Liberia. This report is based primarily on desk research, with quality assurance provided by a country expert.
ZenodoArchiveID: 5652130 previousZenodoArchiveID: 3830953 previousshortDOI: 10/ghgk68 previousDOI: 10.5281/zenodo.3830953 shortDOI: 10/ghgk68 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3830953 10.53832/edtechhub.0033 10/ghgk68 2339240:XCBTX2XL 2405685:2HM2SBVM 2405685:FU7Z8QM7
Keywords: C:Liberia; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH

Deploying an e-Learning Environment in Zanzibar: A Short Guide - Groeneveld, Caspar; Kibga, Elia; Kaye, Tom (EdTech Hub, 2020)
In April 2020, the MoEVT and the World Bank approached the EdTech Hub to explore the feasibility of implementing a Virtual Learning Environment (VLE). The parties agreed on three deliverables to support this work. 1. A practical and actionable report analysing key factors to be considered in deploying an e-learning platform in Zanzibar. 2. A report documenting the process of sourcing appropriate digital content, aligning this content with the curriculum and populating the e-learning system accordingly. 3. An implementation plan to guide the deployment of an e-learning system in Zanzibar. This presentation deck is the third deliverable.
ZenodoArchiveID: 4706000 previousDOI: 10.5281/zenodo.4706000 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3971656 10.5281/zenodo.4706000 10.53832/edtechhub.0029 2129771:YZIID28Y 2339240:7P4VDPLY 2339240:WYT4QCIW 2405685:85C5HVC7 2405685:I86XXKMH
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Using Blended Learning to Support Marginalised Adolescent Girls’ Education: A Review of the Evidence - Allier-Gagneur, Zoé; Chuang, Rachel; McBurnie, Chris; Haßler, Björn (EdTech Hub, 2020)
This topic brief reviews evidence about the use of blended learning to support the education of marginalised adolescent girls in low- and middle- income countries.
ZenodoArchiveID: 4762319 previousDOI: 10.5281/zenodo.4762319 previousDOI: 10.5281/zenodo.4762319 previousDOI: 10.5281/zenodo.3952069 10.5281/zenodo.3952069 2405685:7PYD5JNV 2405685:H3AI5F3C 2339240:ENEKVCE3 2129771:FX6TFDPQ 2129771:9Q4PMCJN 2486141:TE93MW3V KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3952069 10.5281/zenodo.4762319 10.53832/edtechhub.0009 2339240:MU9RJZS3 2339240:WG969BFI 2405685:7PYD5JNV 2405685:A7IA7VZZ 2405685:H3AI5F3C 2405685:XMDKD3TS
Keywords: F: Helpdesk response; H:Blended learning; L:Gender and education; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _zenodo:submitted; _zenodoETH; _zenodoETH:submitted; dode_eth-src-eth; dode_eth-trf2-dode

Girls’ Education and EdTech: A Rapid Evidence Review - Webb, Daniel; Barringer, Katie; Torrance, Rebecca; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of the existing literature on the use of technology in supporting girls’ education in low and middle-income countries (LMICs). The RER has been produced in response to the novel 2019 coronavirus (COVID-19), and the resulting widespread global shutdown of schools. It therefore has an emphasis on transferable insights that may be applicable to educational responses resulting from the limitations to the continuation of schooling caused by COVID-19. Established approaches to maintaining continuity of education for the most marginalised have particular salience during this period because of the significant increase in the number of students at risk of disruption. Research consistently shows that while education across the board is negatively affected by crisis situations, the schooling of girls is disproportionately impacted. The RER aims neither to advocate nor discourage the use of technology in girls’ education in response to the present COVID-19 pandemic, but rather to provide an accessible summary of existing evidence on the topic so that educators, policy makers and donors might make informed decisions about the potential role of technology in delivering education for girls.
ZenodoArchiveID: 4737460 previousDOI: 10.5281/zenodo.4556939 PreviousDOI: 10.5281/zenodo.3958002 PreviousDOI: 10.5281/zenodo.4477168 PreviousShortDOI: 10/ghgnfc Publisher: Zenodo Version Number: 1 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3958002 10.5281/zenodo.3958002 10.5281/zenodo.4477168 10.5281/zenodo.4556939 10.5281/zenodo.4737460 2259720:36F6CWBU 2339240:23GW5XQ8 2339240:6YJ555Q6 2339240:9CAC5BI5 2339240:ABKFKG4Q 2339240:FC5RCEYW 2339240:GCYWZ39Q 2339240:GZYWFIHI 2339240:JMFNCMP8 2339240:L326GM9E 2339240:MQ8QSK5B 2339240:PB295ID7 2339240:Q8QJYXRQ 2339240:TIVTGHAA 2339240:TYYDMDPR 2339240:VFBZXUEM 2339240:VFBZXUEM; 2339240:WVUDHTHF 2405685:4XTHDWDA 2405685:6PE7ANUL 2405685:78VECZYK 2405685:ALEXQL2P 2405685:BLT5KKXG 2405685:C4JLZV3D 2405685:CZBRW85R 2405685:E4TFYPYP 2405685:IV7MEXRW 2405685:NMXFFTIB 2405685:PKS7U5LC 2405685:RTIHY6H8 2405685:S5PCWMRP 2405685:SA26Q7UG 2405685:V7VESTKX 2405685:WR37F768 2405685:YHERHZKV 2405685:YNMUHK9S 2534378:5794CXFP 2534378:5GTJL9K7 4804264:EZB37W4S
Keywords: L:English UXZJW5DR; L:Gender and education; LP: English; P:Evidence review VCMFM9ZD; TAG:E:Primary education QIVZD2B2; TAG:E:Secondary education JS5BG2RE; TAG:F:Access W8TZWAGE; TAG:P:Girls ED5GMBNU; _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _L:English UXZJW5DR; _MELA_seen; _P:Evidence review VCMFM9ZD; _T:E:Primary education QIVZD2B2; _T:E:Secondary education JS5BG2RE; _T:F:Access W8TZWAGE; _T:P:Girls ED5GMBNU; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; _zenodoETH:submitted; ⛔ No DOI found; ⛔ No INSPIRE recid found

Refugee Education: A Rapid Evidence Review - Ashlee, Amy; Clericetti, Giulia; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for education of refugees in low- and middle-income countries (LMICs). The RER has been produced in response to the widespread global shutdown of schools resulting from the outbreak of Covid-19. It therefore has an emphasis on transferable insights that may be applicable to educational responses resulting from the limitations caused by Covid-19. In the current global context, lessons learnt from the use of EdTech in refugee contexts — in which education is often significantly disrupted and education systems and responses are required to rapidly adapt — are salient.
ZenodoArchiveID: 4557019 PreviousDOI: 10.5281/zenodo.4477154 PreviousShortDOI: 10/ghgnf2 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3901521 10.5281/zenodo.4557019 10/ghgnf2 2339240:3KCTC7UA 2339240:5B7T9LEG 2339240:K45TP2GI 2339240:NNZ9DD54 2339240:SIV6ZELZ 2339240:W3ALIEA9 2405685:397HVPFN 2405685:4M9GTG8I 2405685:5AWZGNCG 2405685:6EUNRYPS 2405685:E56IKGK2 2405685:E6DMTNLL 2405685:TXGBLY4U 2405685:UUNEJ7FS 2405685:W9JLL7JV
Keywords: L:Refugees and migrants; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _P:Evidence review VCMFM9ZD; _cover:v3; _zenodo:submitted; _zenodoETH

The Maldives and Sri Lanka: Question & Answer Session - Adam, Taskeen; Kaye, Tom; Haßler, Björn (EdTech Hub, 2020)
EdTech Hub participated in a question and answer session in May 2020 for policymakers in The Maldives and Sri Lanka. The session focused on the challenges and issues in designing effective distance education programmes during the Covid-19 pandemic. This document provides answers to a list of 13 questions received from stakeholders.
ZenodoArchiveID: 5652128 previousZenodoArchiveID: 3885817 previousshortDOI: 10/ghgngv previousshortDOI: 10/ghgngv previousDOI: 10.5281/zenodo.3885817 previousshortDOI: 10/ghgngv EdTechHub.Source: 2405685:HE2Q6Z8Y EdTechHub.Source: <this> shortDOI: 10/ghgngv KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3885817 10.53832/edtechhub.0018 10/ghgngv 2129771:YC82FCEP 2339240:TND87RAP 2405685:HE2Q6Z8Y 2405685:SRU74BP6
Keywords: F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Educational Television: A Rapid Evidence Review - Watson, Joe; McIntyre, Nora (EdTech Hub, 2020)
This Rapid Evidence Review (RER) gives an overview of the recent literature concerning how the use of educational television might support children’s learning in low- and middle-income countries (LMICs). In this review, educational television is defined as television designed with research-based knowledge of how children use and understand television that systematically incorporates academic or social curricula into its content. In low-income contexts, educational television material could be delivered through videos played in schools that are supported by corresponding teacher guidance (e.g. the Mexican school-based T elesecundaria programme), or broadcast on public channels (e.g. the Tanzanian animation, Ubongo Kids). As such, certain educational television projects are capable of functioning even in circumstances where access to formal schooling facilities is restricted. This review therefore provides information that is particularly valuable in the context of the COVID-19 pandemic.
ZenodoArchiveID: 4556935 PreviousDOI: 10.5281/zenodo.4476991 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3956366 10.5281/zenodo.3956366 10.5281/zenodo.4476991 10.5281/zenodo.4556935 2259720:BFY7A76P 2339240:3WZUWHB3 2339240:CVI8639W 2339240:G8MSWBJC 2339240:IF3IMDSW 2339240:NUYRVP8T 2339240:UXMEFECL 2405685:BVXSZ7G4 2405685:BZFLWXG6 2405685:DPRU64AB 2405685:FMULV6ZI 2405685:TJ95P4G4 2405685:UJF6X47J 2405685:UVB294JN 2405685:Y3XDX8FW 4803016:WC4XVPPN
Keywords: L:English UXZJW5DR; P:Evidence review VCMFM9ZD; TAG:E:Primary education QIVZD2B2; TAG:E:Secondary education JS5BG2RE; TAG:F:Access W8TZWAGE; TAG:P:Girls ED5GMBNU; _DOILIVE; _EdTechHub_Output; _GS:indexed; _L:English UXZJW5DR; _MELA_seen; _P:Evidence review VCMFM9ZD; _T:E:Primary education QIVZD2B2; _T:E:Secondary education JS5BG2RE; _T:F:Access W8TZWAGE; _T:P:Girls ED5GMBNU; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH

Accelerated Learning and EdTech: A Rapid Evidence Review - Damani, Kalifa (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of the existing literature on the use of accelerated learning in low- and middle-income countries (LMICs), with a focus on how EdTech might best be utilised for accelerated learning. It begins with a broad discussion of the components of accelerated learning, followed by a more focused discussion on how accelerated learning has been used to enhance learning outcomes for marginalised groups in LMICs. An exploration of how EdTech can be utilised for accelerated learning is then presented.
ZenodoArchiveID: 4556941 Note: This item replaced a previous version with DOI 10.5281/zenodo.4071441. PreviousDOI: 10.5281/zenodo.4071441 PreviousDOI: 10.5281/zenodo.4477135 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.4556941 10.5281/zenodo.4071441 10.5281/zenodo.4477135 10.5281/zenodo.4556941 2339240:785U4JZJ 2339240:9MZRHWYE 2339240:TQLWMAIZ 2405685:9BWHLEWZ 2405685:I4UFGAQA 2405685:JV5JCGN3 2405685:XNYSHYYD
Keywords: L:Gender and education; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _P:Evidence review VCMFM9ZD; _cover:v2; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Deploying an e-learning Environment in Zanzibar: Digital Content Curation - Groeneveld, Caspar; Kibga, Elia; Kaye, Tom (EdTech Hub, 2020)
In April 2020, the Zanzibar Ministry of Education and Vocational Training (MoEVT) and the World Bank approached EdTech Hub (the Hub) to explore the feasibility of implementing a Virtual Learning Environment (VLE). The MoEVT, the World Bank and the Hub agreed that the Hub would work with the MoEVT to develop the following 1. A practical and actionable report analysing key factors to be considered in deploying an e-learning platform in Zanzibar. 2. A report documenting the process of sourcing appropriate digital content, aligning this content with the curriculum and populating the e-learning system accordingly. 3. An implementation plan to guide the deployment of the e-learning system. This document addresses the second part of the request and is an elaboration of the digital content selection, curation, and adaptation process suggested in the first report. However, this document is a stand-alone piece that does not require familiarity with any of the other deliverables.
ZenodoArchiveID: 3966976 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3966976 2129771:XMGQ4JQJ 2339240:L5RLM582 2339240:R72E853W 2405685:T2W7MU3K 2405685:U49W6LTF 2405685:ZI8PHKCC
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; ___working_potential_duplicate; _cover:v2; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Technology-Supported Personalised Learning: A Rapid Evidence Review - Major, Louis; Francis, Gill A. (EdTech Hub, 2020)
This publication is one part of a series of rapid evidence reviews that has been produced by the EdTech Hub. The purpose of the rapid evidence reviews is to provide education decision-makers with accessible evidence-based summaries of good practice in specific areas of EdTech. They are focused on topics which are particularly relevant in the context of widespread global challenges to formal schooling as a result of COVID-19. All the rapid evidence reviews are available at edtechhub.org.
ZenodoArchiveID: 4556925 PreviousDOI: 10.5281/zenodo.3948175 PreviousDOI: 10.5281/zenodo.4477170 PreviousShortDOI: 10/gg7sp2 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3948175 10.5281/zenodo.3948174 10.5281/zenodo.3948175 10.5281/zenodo.4477170 10.5281/zenodo.4556925 2339240:6NYL4Q6K 2339240:782897NS 2339240:CQIWZXYK 2339240:FFVXKB6Y 2339240:FH2WAXTQ 2339240:KAWEDEAZ 2339240:L9THHN3N 2339240:P8B4HPZC 2339240:QLA593HB 2339240:T58E6LDA 2339240:T8L6PTRX 2339240:VZBB4HAF 2405685:839AFBBS 2405685:89H7NAA7 2405685:A2II5ZV7 2405685:A49KTEL6 2405685:AT6JS3QN 2405685:CJR7PMKJ 2405685:DEXS2WA8 2405685:FFSBB3JJ 2405685:NQSPAG3I 2405685:RVZFVD7G 2405685:U95XV67E 2405685:WJRBJQBN 2534378:8FA5G2KF
Keywords: F: Evidence review; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH

Education Sector Analysis. Assessing the enabling environment for gender equality - Republic of Sierra Leone (UNICEF, IIEP - UNESCO, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:X5MR76ZW 2405685:29U93GQF

Back-to-School Campaigns Following Disruptions to Education - Chuang, Rachel; Kaye, Tom; Moss Coflan, Caitlin; Haßler, Björn (EdTech Hub, 2020)
This EdTech Hub Helpdesk response focuses on back-to-school campaigns following disruptions to education, ensuring that children rapidly return to school as soon as it is safe and practical. Key themes of effective school re-openings are examined in the context of modalities used to deliver distance learning (e.g., radio, television).
ZenodoArchiveID: 3878423 previousshortDOI: 10/ghgk6n previousshortDOI: 10/ghgk6n previousDOI: 10.5281/zenodo.3878423 previousshortDOI: 10/ghgk6n EdTechHub.Source: 2405685:DS66UGW4 EdTechHub.Source: <this> shortDOI: 10/ghgk6n KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3878423 10.53832/edtechhub.0019 10/ghgk6n 2129771:GKIQY5RP 2339240:29BIZJM5 2339240:WSA5X76N 2405685:4Z5W36SI 2405685:DS66UGW4 2405685:IS587WTH
Keywords: COV:COVID and reopening of schools; F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Deploying an e-Learning Environment in Zanzibar: Feasibility Assessment - Groeneveld, Caspar; Kibga, Elia; Kaye, Tom (EdTech Hub, 2020)
The Zanzibar Ministry of Education and Vocational Training (MoEVT) and the World Bank (the Bank) approached the EdTech Hub (the Hub) in April 2020 to explore the feasibility of implementing a Virtual Learning Environment (VLE). The Hub was requested to focus primarily on the deployment of a VLE in lower secondary education, and this report consequently focuses primarily on this group. The report is structured in four sections: An introduction to provide the background and guiding principles for the engagement with a short overview of the methodology applied. An analysis of the Zanzibar education system with a particular focus on elements relevant to deploying a VLE. This includes the status of ICT infrastructure, and a summary of the stakeholders who will play a role in using or implementing a VLE. A third section that discusses types of VLEs and content organisation, and their applicability to the Zanzibar ecosystem. A conclusion with recommendations for Zanzibar, including short- and long-term steps. In this collaboration with Zanzibar’s MoEVT, the Hub team sought to understand the purpose of the proposed VLE. Based on discussions and user scenarios, we identified two main education challenges a VLE may help to resolve. In the short term, students cannot go to school during the COVID-19 crisis, but need access to educational content. There is content, but no flexible and versatile platform to disseminate content to all students. In the long term, a mechanism to provide students with access to quality, curriculum-aligned content in school, or remotely, is required.
ZenodoArchiveID: 5652121 previousZenodoArchiveID: 3941727 previousDOI: 10.5281/zenodo.3941727 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3941727 10.53832/edtechhub.0028 2129771:KLLMDHKK 2339240:Y5Z46TRU 2405685:2B8SH5S3 2405685:K7JDL4IL
Keywords: C:Tanzania; H:Online learning; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Pakistan Topic Brief: Providing Distance Learning to Hard-to-reach Children - Baloch, Imdad; Kaye, Tom; Koomar, Saalim; McBurnie, Chris (EdTech Hub, 2020)
This brief explores the use of EdTech to support distance learning in Pakistan. Specifically, it explores ways to provide distance education to children in remote rural areas and urban slums.
ZenodoArchiveID: 5652066 previousZenodoArchiveID: 3885606 previousshortDOI: 10/ghgnfw previousDOI: 10.5281/zenodo.3885606 EdTechHub.Copy: 2129771:VAP9K6BW EdTechHub.Copy: 2129771:VAP9K6BW shortDOI: 10/ghgnfw KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3885606 10.5281/zenodo.3885606 10.53832/edtechhub.0026 10/ghgnfw 2129771:IK97VLY8 2129771:MXTVUGAA 2129771:VAP9K6BW 2339240:2ZVLRPTQ 2339240:7PXTZ2FQ 2339240:ZE9V9N4R 2405685:8IJT433J 2405685:9TKV7H6E 2405685:BBLQFJKE 2405685:IDL75DHT 2405685:WMUEC2ZV 2405685:Z2VNN7ER
Keywords: F: Helpdesk response; L:Out-of-school populations; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; _cover:v1; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode